Penambahan asap cair mampu mempertahankan profil asam lemak ikan tuna kering blok - Jusuf Leiwakabessy; Max Robinson Wenno (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Dry fish block is a food product from by-product of tuna loin. It is salted, liquid smoked, and dried.This study was aimed to determine fatty acid profile of the dry fish block after the addition of liquid smoke.The dry fish block was composed of twelve saturated fatty acids (SFA), six monounsaturated fatty acids(MUFA), and nine polyunsaturated acids (PUFA). The total of SFA in dry fish block without and with liquidsmoke was 19.94% and 21.29%, while MUFA was 9.35% and 11.77% and PUFA was 14.45% and 16.04%,respectively.